Mediating effects of self-esteem and self-compassion on the relationship between body dissatisfaction and depression among adolescents with polycystic ovary syndrome - Huangfu, Huihui; Li, Li; Shuai, Wen (Frontiers in Public Health, 2024)
Introduction: Body dissatisfaction significantly impacts depression among adolescents with polycystic ovary syndrome (PCOS). This relationship is compounded by various factors. Our study aims to explore the roles of self-esteem and selfcompassion in the relationship between body dissatisfaction and depression in adolescent with PCOS. Methods: A cross-sectional study was conducted at the Shanghai First Maternity and Infant Hospital, involving 287 adolescents diagnosed with PCOS from January 2020 to December 2021. Participants completed validated questionnaires covering body dissatisfaction, self-esteem, self-compassion and depression. We utilized correlation and mediation analyses to examine the relationships and mediating effects among these variables.Results: Body dissatisfaction had a significant positive effect on depression (β=4.254, p<0.001). Conversely, self-esteem (β=-0.944, p<0.001) and self-compassion (β=-0.318, p<0.001) were negative predictors of depression. Both self-esteem (β=3.405, 95% CI=(0.151, 0.305)) and self-compassion (β=1.525, 95% CI=(0.045, 0.165)) were shown to partially mediate the relationship between body dissatisfaction and depression, explaining 37.07% and 16.61% of the total effect, respectively.This study highlights the importance of fostering self-esteem and selfcompassion among adolescents with PCOS to buffer the depressive effects of body dissatisfaction. Interventions aimed at promoting accurate and positive body perceptions, enhancing self-esteem, fostering a supportive attitude towards personal challenges, and maintaining positive emotional states are recommended to decrease the incidence of depression.